Age Is No Longer a Limit: Two Cases of Hepatectomy in Patients Over 90 Years Old - Shugo Uwatoko; Kentaroh Yamamoto; Takamitsu Sasaki; Daisuke Fukumori; Hirotsune Igimi; Mami Yamamoto; Fumio Yamamoto; Yuichi Yamashita (Case Reports in Gastroenterology, 2015)
Hepatocellular carcinoma (HCC) is a common malignant tumor with poor prognosis. The age of patients affected by HCC is considered to be increasing, and several studies have reported significantly higher rates of morbidity and mortality after hepatectomy for HCC in elderly patients. However, other studies have reported that the short- and long-term outcomes of surgery for HCC in elderly patients are similar to those in younger patients. Whether the indications for hepatic resection in elderly patients resemble those in younger patients has thus been questioned. We describe two cases of patients over 90 years old who underwent major hepatectomy for HCC, representing the oldest patients in the world to have done so.